2016
DOI: 10.1530/eje-15-1118
|View full text |Cite
|
Sign up to set email alerts
|

ENDOCRINE TUMOURS: The genomics of adrenocortical tumors

Abstract: The last decade witnessed the emergence of genomics, a set of high-throughput molecular measurements in biological samples. These pan-genomic and agnostic approaches have revolutionized the molecular biology and genetics of malignant and benign tumors. These techniques have been applied successfully to adrenocortical tumors. Exome sequencing identified new major drivers in all tumor types, including KCNJ5, ATP1A1, ATP2B3 and CACNA1D mutations in aldosterone-producing adenomas (APA), PRKACA mutations in cortiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 97 publications
0
31
0
1
Order By: Relevance
“…In recent years, several multicenter studies have shed light on the pathogenesis of ACC (5,6,7,8), but 'multi-omic' studies (9,10,11) reveal that only a minority of ACC cases have pathogenic driver mutations. For details on this topic, we refer to recent reviews (12,13,14).…”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
“…In recent years, several multicenter studies have shed light on the pathogenesis of ACC (5,6,7,8), but 'multi-omic' studies (9,10,11) reveal that only a minority of ACC cases have pathogenic driver mutations. For details on this topic, we refer to recent reviews (12,13,14).…”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
“…These results can help us to further understand the role of DEGs in the development and progress of ACC. The additional KEGG pathway analysis showed that up‐regulated DEGs were significantly enriched in cell cycle, cell senescence, progesterone‐mediated oocyte maturation, oocyte, p53 signalling pathway and folic acid resistance, further confirmed the important roles of p53 signalling pathway in ACC …”
Section: Discussionmentioning
confidence: 65%
“…Mutations in the TP53 tumor suppressor gene, abnormal Wnt activation, and insulin-like growth factor 2 overexpression have been reported in ACCs (11). Analysis of mRNA expression, DNA methylation, and microRNA expression profiles in ACC delineates 2 main subgroups with differences in overall survival rate (12). Multistep tumorigenesis models are well-documented in many solid tumors, such as colorectal carcinoma, but it is still a matter of debate whether multistep tumorigenesis occurs in ACC.…”
Section: Discussionmentioning
confidence: 99%